(untitled) (Studia theodisca, 2020)
Patrick Süskind’s Das Parfum: Die Geschichte eines Mörders presents a sort of Janus-figure, gazing backwards toward the primitive form of life (Grenouille’s Romantic deliverance) and forward toward an Enlightenment anthropocentric mechanism (an allusion to negative aesthetics) which reveals the formation and dissolution of political power through the olfactory experiences of the protagonist. In other words, it concerns the two worlds between which there is an unknown force transforming all olfactory manipulation/experimentation into nothingness: as men scheme their evil business through objects or scents, a greater force then deconstructs those schemes.